Regulation of RNA polymerase sigma subunit synthesis in Escherichia coli: intracellular levels of sigma 70 and sigma 38. - Jishage, M (1995)
The intracellular levels of two principal sigma subunits, sigma 70 (sigma D, the rpoD gene product) and sigma 38 (sigma s, the rpoS gene product), in Escherichia coli MC4100 were determined by a quantitative Western immunoblot analysis. Results indicate that the level of sigma 70 is maintained at 50 to 80 fmol per micrograms of total proteins throughout the transition from the exponential growth phase to the stationary phase, while the level of sigma 38 protein is below the detection level at the exponential growth phase but increases to 30% of the level of sigma 70 when cell growth stops to enter into the stationary phase. Beside the stationary phase, the increase in sigma 38 level was observed in two cases: exposure to heat shock at the exponential phase and osmotic shock at the stationary phase.